Cytochrome P450-mediated metabolism and cytotoxicity in rat cultured hepatocytes - Hammond, Alison H. (1990)
The aim of this investigation was to define the in vitro conditions necessary to support cytochrome P450-mediated metabolism in rat cultured hepatocytes, such that this system could then be used as an in vitro model in the study of cytochrome P450-mediated cytotoxicity.